Nomenclature of Non-alcoholic Equivalents of Alcoholic Beverages Used on the Polish Market in the Light of National and EU Legal Regulations - Kamińska, Anna; Dmowski, Przemysław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The main aim of the study was to demonstrate how the lack of appropriate regulations affects the nomenclature used for non-alcoholic equivalents of alcoholic beverages available on the Polish market, and thus highlight the problems that arise from the lack of regulation for consumers and producers. Research Design & Methods: A semantic and comparative analysis of the names appearing on the labels of non-alcoholic equivalents of alcoholic beverages available on the Polish market was conducted. The research methods used include desk research and document research, including legal-dogmatic analysis and observation. Findings: The lack of clear legal requirements for the nomenclature of non-alcoholic equivalents of alcoholic beverages was revealed. It was found that there are discrepancies in the names of products in the product categories studied, and it was established that both products containing up to 0.5% and those with 0.0% alcohol by volume are mostly labelled under the same name (“non-alcoholic”). This can cause a number of doubts not only among consumers, but also among the entities labelling the goods. Implications / Recommendations: Given this state of affairs, it would make sense to introduce regulations to provide guidelines for the nomenclature and labelling of such products in order to ensure food safety and protect consumers. Contribution: Using proper, accurate nomenclature on alcoholic beverage substitutes is crucial for supporting management decision-making and conducting marketing activities that guarantee reliable and lawful information for consumers.